Analysis of cardiac toxicity after definitive chemoradiotherapy for esophageal cancer using a biological dose–volume histogram. (13th February 2020) - Takeuchi, Yuki; Murakami, Yuji; Kameoka, Tsubasa; Ochi, Masanori; Imano, Nobuki; Takahashi, Ippei; Nishibuchi, Ikuno; Kimura, Tomoki; Kawahara, Daisuke; Saito, Akito; Nagata, Yasushi
Abstract: This study aimed to evaluate the relationship between cardiac toxicity after definitive chemoradiotherapy (CRT) for esophageal cancer and the dose–volume histogram (DVH) of organs at risk (OARs) [using biological effective dose (BED)]. We analyzed the data of 83 patients with esophageal cancer treated using definitive CRT between 2001 and 2016. Furthermore, we evaluated pericardial effusion (PE) as a measure of cardiac toxicity. The median total irradiation dose was 60 (50.4–71) Gy. Symptomatic PE was observed in 12 (14%) patients. The heart and pericardium V5–V100-BED were significantly higher in patients with symptomatic PE than in those without symptomatic PE (heart: V5–V95-BED, P < 0.001; V100-BED, P = 0.0053, and pericardium: V5–V40-BED, V55–V95-BED, P < 0.001; V45–50-BED, V100-BED, P < 0.05, respectively). Receiver operating characteristic curve analysis showed that the dose–volume parameter of the pericardium and the heart that was most strongly associated with an adverse cardiac event was V80-BED, and the mean dose and the cut-off value were 27.38% and 61.7 Gy-BED, respectively. Multivariate analysis showed that the pericardium V80-BED and the mean heart dose-BED were risk factors for symptomatic PE ( P < 0.001, respectively). We revealed the relationship between the irradiated dose of the OARs and symptomatic PE using a BED-based dose–volume histogram. Pericardium V80-BED and mean heart dose-BED were the most relevant risk factors for symptomatic PE.